Arabic Computational Linguistics Between Interest and Achievement - Alshraideh , Safa (Dirasat: Human and Social Sciences, 2023)
Objectives: This study aims to shed light on the efforts made in the Arab scientific community in computing the Arabic language. Methods: The study was based on the investigative method in tracking the achievements in computational linguistics in Arab universities, including Jordanian universities. This was measured by tracking the courses taught in universities in the Arabic language and computer departments, and research papers and university theses published on the “Dar Al-Manzoma” website, in the 1999-2022. Results: Arab universities teach computational linguistics in very narrow limits as an independent discipline. The proportion of the research publications in this field, whether in the form of research papers or university theses is limited, if compared to the research outputs in other linguistics disciplines; the percentage of contributions for that was 0.9%. The survey of theses in this field shows that there is no twinning between the Arabic language and computer departments at all. Conclusions: The study recommends that twinning between the Arabic language departments and computer departments is necessary in the research and applied work. It also recommends the importance of introducing courses of computational linguistics in universities in the Arabic and computer departments in graduate programs and directing attention to increasing the research product in this field, designing programs and applications too.